1992
DOI: 10.1128/jvi.66.1.204-216.1992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the RNA packaging-defective retrovirus SE21Q1b

Abstract: The nonconditional RNA packaging mutant SE21Q1b contains cis-and transacting defects which cause cellular mRNA, rather than viral genomic RNA, to be nonspecifically packaged into SE21Q1b viral particles. Using genomic libraries of the c-SE21Qlb quail cell line, we have been able to construct a molecular clone of the SE21Q1b provirus. Upon transfection into primary quail embryo fibroblasts, the SE21Q1b molecular clone is able to recapitulate the nonspecific RNA packaging phenotype of the c-SE21Q1b cell line. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0
3

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
3
13
0
3
Order By: Relevance
“…A cluster of differences in the C terminus of the NC domain, when tested in a wild-type background, did not reconstitute the mutant phenotype (2). The results reported here are consistent with those of Anderson et al (2), who suggest that the behavior of SE21Q1b Gag is not due to a single defect.…”
supporting
confidence: 93%
“…A cluster of differences in the C terminus of the NC domain, when tested in a wild-type background, did not reconstitute the mutant phenotype (2). The results reported here are consistent with those of Anderson et al (2), who suggest that the behavior of SE21Q1b Gag is not due to a single defect.…”
supporting
confidence: 93%
“…We also observed that the HIV-1 mutant containing the M-MuLV NC domain was able to encapsidate a nonviral RNA 20-fold more efficiently than was wild-type HIV-1, indicative of an increased nonspecific packaging activity in the mutant. This phenotype is reminiscent of the avian SE21Q1b mutant, which packages cellular RNAs because of ill-defined mutations in the Gag polyprotein (2,34). However, the HIV-1 mutant containing the M-MuLV NC domain appears not to package RNAs strictly on a nonspecific basis, as the mutant also displayed an ability to specifically recognize the M-MuLV ⌿ element.…”
Section: Discussionmentioning
confidence: 99%
“…Для вырезания (сплайсинга) части транскрипта, соот ветствующей генам gag и рої, в провирусе имеются две сигнальные последовательности -sa, sd. Ге номная РНК упаковывается вирусными белками при участии цис-активных упаковочных последова тельностей (40, находящихся между уникальным Ш-участком и началом gag [2][3][4][5][6][7][8][9].…”
unclassified
“…-сигналы упаковки; У -ген неомицинфосфотрансферазы; 2 -ген гигромицинфосфотрансферазы; 3 -тимидинкиназный ген HSV; Promoter -внутренний промотор; IRES -внутренний рибосомный повторяющийся сайт [2,10]. Делегирование ^-упаковочных последова тельностей и точечные мутации в gag-гене наруша ют процесс узнавания Ga^-белком специфической вирусной РНК.…”
unclassified
See 1 more Smart Citation